2010
DOI: 10.1007/s11244-010-9604-7
|View full text |Cite
|
Sign up to set email alerts
|

Ring Opening of Decalin Over Zeolite-Supported Iridium Catalysts

Abstract: Selective ring opening of decalin was investigated over various metal-modified zeolites in order to shed light on the key parameters affecting the selectivity to ringopening products at low extent of cracking reactions. Ir-modified zeolites H-Y and H-Beta having different concentration and strength of acid sites were studied in a batch reactor at 250-310°C and 20-60 bar H 2 and their performance was compared with that of Pt-modified zeolites. The concentration of Brønsted acid sites, reaction temperature and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 21 publications
(36 reference statements)
0
27
0
Order By: Relevance
“…By contrast, extremely scant information is available concerning the formation or not of open‐chain decanes. In a few reports the occurrence of decane isomers was qualitatively mentioned 104. 106, 107 In just one paper quantitative yields of open‐chain decanes formed in the hydroconversion of decalin on a Pt,Ir/H‐Y zeolite were given: their maximum yield was reported to be 4 % 108.…”
Section: Selective Ring Opening Of Multi‐ring Naphthenes Derived Fmentioning
confidence: 99%
“…By contrast, extremely scant information is available concerning the formation or not of open‐chain decanes. In a few reports the occurrence of decane isomers was qualitatively mentioned 104. 106, 107 In just one paper quantitative yields of open‐chain decanes formed in the hydroconversion of decalin on a Pt,Ir/H‐Y zeolite were given: their maximum yield was reported to be 4 % 108.…”
Section: Selective Ring Opening Of Multi‐ring Naphthenes Derived Fmentioning
confidence: 99%
“…In previouss tudies, most of the supported metal catalysts, such as supported Pt, Pd, Ru,R h, Fe, and Ni catalysts, suffer from high selectivity to decarbonylation or decarboxylation products rather than hydrodeoxygenation products even under H 2 . [6][7][8][9][10][11][12][13][14] Few catalysts,i ncluding Niloaded Hb zeolite, [16] Pt-Re/ZSM-5, [17] Pt/Nb 2 O 5 , [18] Pd/Nb 2 O 5 / SiO 2 , [19] tungsten-or molybdenum-based catalysts, [20][21][22][23] Ni-Mo/ Al 2 O 3 , [24] and hydrodesulfurization catalysts [25] (sulfided NiMo oxides), catalyze the selective hydrodeoxygenation of fatty acids under pressurized H 2 .H owever,m ost of these systems have some drawbacks such as decarbonylation and cracking as side reactions and the necessity of high catalyst loading or,i n other words, low turnover numbers (TONs). In our previous study, [18] we reported that Pt/Nb 2 O 5 showed a6 0times higher TON for hydrodeoxygenation of af atty acid than Ni-loaded Hb zeolite [16] and tungsten-or molybdenum-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The metal sites would be responsible for producing the C-C bond cleavage, while the acid function is needed to produce the preliminary ring contraction (RC) from 6 to 5 carbons, the latter being easier to open. However, very strong acid sites can lead to excessive cracking [2][3][4][5][6][7][8][9][10]. The activity and selectivity of the RO in bifunctional catalysts is strongly dependent on the properties of the metal and the support as well as on the reaction conditions.…”
Section: Introductionmentioning
confidence: 99%